2006
DOI: 10.1063/1.2364895
|View full text |Cite
|
Sign up to set email alerts
|

Starlike dendrimers in solutions: Structural properties and internal dynamics

Abstract: We measured the shape and the internal dynamics of starlike dendrimers under good solvent conditions with small-angle neutron scattering and neutron spin-echo ͑NSE͒ spectroscopy, respectively. Architectural parameters such as the spacer length and generation were varied in a systematic manner. Structural changes occurring in the dendrimers as a function of these parameters are discussed, i.e., in terms of the fractal dimension and deviations of the radius of gyration from the Gaussian value. A first cumulant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
(75 reference statements)
2
14
0
Order By: Relevance
“…Thus, the minimum became increasingly deep with increasing generation number, while the deviations from the pre-averaged values (whose minimum occurs at qR g ≈ 2.5) increase somewhat; it may thus be concluded that, as expected, pre-averaging leads to larger errors with higher degrees of branching. Such theoretical predictions are in semi-quantitative agreement with neutron spin echo experimental results obtained for dendrimers with a six-functional core (f = 6) and binary dendra (m = 2) with relatively long and flexible spacers between adjacent branch points [52]. In fact, a deep minimum was measured in the plot of Ω(q)/q 3 as a funtion of qR g .…”
Section: Analytical Approachessupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, the minimum became increasingly deep with increasing generation number, while the deviations from the pre-averaged values (whose minimum occurs at qR g ≈ 2.5) increase somewhat; it may thus be concluded that, as expected, pre-averaging leads to larger errors with higher degrees of branching. Such theoretical predictions are in semi-quantitative agreement with neutron spin echo experimental results obtained for dendrimers with a six-functional core (f = 6) and binary dendra (m = 2) with relatively long and flexible spacers between adjacent branch points [52]. In fact, a deep minimum was measured in the plot of Ω(q)/q 3 as a funtion of qR g .…”
Section: Analytical Approachessupporting
confidence: 87%
“…The minimum occurred at ≈ 2.5–3, and thus was close to the calculated value, although somewhat deeper, while the increase of at smaller than 2.5 was sharper than calculated, but smoother at higher values. We note, incidentally, that in the same paper [ 52 ], the corresponding linear polymer followed the theoretical prediction of Equation (11). Furthermore, it should be added that in a previous paper of the same group [ 53 ], analogous neutron scattering experiments carried out on PAMAM dendrimers (which had a much shorter spacer length than the sample mentioned previously) with generations up to g = 8 only displayed a diffusive behavior, while the intramolecular dynamics were too slow to be effectively recognized.…”
Section: Theoretical and Simulation Results For Directly Observablmentioning
confidence: 69%
“…NMR [46,51,59,60], neutron scattering [61][62][63], dielectric relaxation spectroscopy [64,65], rheology [66], fluorescence anisotropy [67], and molecular and Brownian dynamics computation [68][69][70][71] have provided some information about the mobility of the different segments constituting a dendrimer, generally via the rotational correlation time (τ C ) of the segments. The overall conclusion of these studies is that the chain ends are more mobile than the internal segments, and that their rotational correlation time is not much affected by increasing G values.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of fractals in polymers that involved modeling and/or simulation include Janke & Schakel (2005), Lo Verso et al (2006 and Marcone et al (2007). On the other hand, Rathgeber et al (2006) have done some work on theoretical modeling and experimental studies of dendrimers. There have also been experimental studies of crystal pattern transition from dendrites through fourfold-symmetric structures to faceted crystals of ultra thin poly(ethylene oxide) films which were carried out by .…”
Section: Solubilitymentioning
confidence: 99%